Design and Development of an Estate Management System for Griya Gardenia Indah - Normalisa, Normalisa; Atmadiputra, Pradana; Chandra, Zahran Nurafi (Program Studi Teknik Informatika Universitas Pamulang, 2024)
This research introduces an innovative solution, an Estate Management System, tailored for Griya Gardenia Indah, a subsidiary of Cipta Harmoni Lestari. Facing multifaceted challenges in estate management, this study aims to develop a centralized and intuitive web application utilizing modern technologies such as Vue.js, Strapi, MySQL, HTML, CSS, JS, and PHP. The system targets streamlined estate processes, improved data accessibility, and efficient communication channels between administrators and residents across four real estate projects. By employing an iterative development approach, stakeholder engagement, and rigorous testing, this research aims to transform estate management practices, enhance operational efficiency, and elevate resident satisfaction. The study navigates through an organization profile, literature review, methodology, results, and recommendations, culminating in a comprehensive solution poised to revolutionize estate administration practices at Griya Gardenia Indah.